2015
DOI: 10.15171/mejdd.2016.05
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Hybrid Therapy and Standard Triple Therapy for Helicobacter pylori Eradication in Patients with Uremia: A Randomized Clinical Trial

Abstract: BACKGROUND The prevalence of peptic ulcer disease in hemodialysis patients is more than the general population. They are also more prone to complications including upper gastrointestinal bleeding. The aim of this study was to compare the efficacy of 14 days hybrid regimen with 14 days triple therapy for Helicobacter pylori (H. pylori ) eradication in hemodialysis patients. METHODS Forty hemodialysis patients with naïve H.pylori infection were randomized to receive either hybrid regimen (pantoprazole 40 mg + a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A pilot study of hybrid therapy showed that it achieved an eradication rate of 97.4% by intention‐to‐treat (ITT) analysis and 99.1% by per‐protocol (PP) analysis in Taiwan 5 . A subsequent randomized controlled trial from Iran, an area with high clarithromycin resistance, demonstrated that 14‐day hybrid therapy achieved a higher eradication rate than 14‐day standard triple therapy 10 . Several randomized controlled trials demonstrated that 14‐day hybrid therapies were comparable or more effective than 10‐day sequential therapies 11–15 .…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study of hybrid therapy showed that it achieved an eradication rate of 97.4% by intention‐to‐treat (ITT) analysis and 99.1% by per‐protocol (PP) analysis in Taiwan 5 . A subsequent randomized controlled trial from Iran, an area with high clarithromycin resistance, demonstrated that 14‐day hybrid therapy achieved a higher eradication rate than 14‐day standard triple therapy 10 . Several randomized controlled trials demonstrated that 14‐day hybrid therapies were comparable or more effective than 10‐day sequential therapies 11–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as per our results we can confer that 12 days' treatment gives ideal result but 10 days' treatment is also accepted. [12][13] According to studies by other countries the eradication rate was acceptable in 14 days' treatment, or in some cases a shorter a shorter duration of treatment could also be accepted. In 2013, a study was carried out where Zullo and his colleagues showed that the H. pylori eradication was made possible by a 5 days' treatment plan in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…For meta‐analysis aimed at updating the Japanese guideline for H. pylori infection in clinical practice, this meta‐analysis was conducted using data from RCTs and observational cohort study identified by searching the medical literature on two kinds of databases, namely PubMed and Cochrane Library databases (Figure S2). We divided studies investigated the efficacy and safety of eradication therapy for patients receiving HD into three categories: (1) comparison of patients receiving HD with healthy individuals having normal renal function using observational cohort study (Study 1, Table 1) [26–33], (2) comparison of patients receiving HD with patients with non‐HD CKD based on observational cohort study (Study 2, Table 2) [29, 30, 32, 34], and (3) randomized controlled trial among patients receiving HD (Study 3, Table 3) [29, 31, 33, 35–39]. We compared H. pylori eradication rates of first‐line therapy lasting for 7–14 days among patients receiving HD.…”
Section: Meta‐analysis Of H Pylori Eradication Therapy For Patients R...mentioning
confidence: 99%
“…1, Table1)[26][27][28][29][30][31][32][33], (2) comparison of patients receiving HD with patients with non-HD CKD based on observational cohort study (Study 2, Table2)[29,30,32,34], and (3) randomized controlled trial among patients receiving HD (Study 3, Table3)[29,31,33,[35][36][37][38][39]. We compared H. pylori eradication rates of first-line therapy lasting for 7-14 days among patients receiving HD.Abbreviations: AMPC, amoxicillin; AZM, azithromycin; bid, twice-daily dosing; CAM, clarithromycin; CIP, ciprofloxacin; EPZ, esomeprazole; FUR, furazolidone; HD, hemodialysis; ITT, intention-to-treat; LPZ, lansoprazole; LVFX, levofloxacin; NA, not available; od, once-daily dosing; OPZ, omeprazole; PP, per protocol; PPI, proton pump inhibitor; PPZ, pantoprazole; RCT, randomized control trial; TNZ, tinidazole.…”
mentioning
confidence: 99%